Six Sigma Evaluation Using Bias Calculated from Internal Quality Control and External Quality Assurance Data: Six Sigma Evaluation of 17 Biochemistry Parameters - Çevlik, Tülay; Haklar, Goncagül (Journal of Medical Biochemistry, 2023)
BackgroundSix Sigma is a popular quality management system that enables continuous monitoring and improvement of analytical performance in the clinical laboratory. We aimed to calculate sigma metrics and quality goal index (QGI) for 17 biochemical analytes and compare the use of bias from internal quality control (IQC) and external quality assurance (EQA) data in the calculation of sigma metrics.MethodsThis retrospective study was conducted in Marmara University Pendik E&R Hospital Biochemistry Laboratory. Sigma metrics calculation was performed as (TEa−bias)/CV). CV was calculated from IQC data from June 2018- February 2019. EQA bias was calculated as the mean of % deviation from the peer group means in the last seven surveys, and IQC bias was calculated as [(laboratory control result mean–manufacturer control mean)/manufacturer control mean)x100]. In parameters where sigma metrics were
Keywords: Six Sigma method; quality goal index; quality management; imprecision; bias